A Significant Role of Soluble Programmed Death Ligand(sPDL-1) in a Progressive Infection Among Patients with Omicron SARS-CoV-2 - M. Abbas, Zainab; Y. Fadhil, Hula (Al-Nahrain Journal of Science, 2025)
Immune checkpoint inhibitors (ICIs) are thought to be critical in developing COVID-19. Even if Omicron had a lower risk of hospitalization and mortality than other variants, some progress has been observed. Programmed cell death-1 (PD-1) is an essential ICI target because it suppresses immune cell activity and serves as a fatigue signal for immune cells. To determine the function of soluble Program Death-Ligand1 (sPD-L1) in SARS-CoV-2 (Omicron variant) infection progression and its relation with biomarkers. A case-control study (43 COVID-19 patients and 30 healthy controls) was tested for the Omicron variant infection by real-time PCR, and the biomarker and sPD-L1 were measured with an ELISA kit. Median sPD-L1 levels in infected individuals were significantly higher than in healthy controls (1079 pg/mL vs. 618.8 pg/mL; p